Coral restoration: Socio-ecological perspectives of benefits and limitations. (January 2019) - Hein, Margaux Y.; Birtles, Alastair; Willis, Bette L.; Gardiner, Naomi; Beeden, Roger; Marshall, Nadine A.
Abstract: Coral restoration is increasingly used globally as a management tool to minimize accelerating coral reef degradation resulting from climate change. Yet, the science of coral restoration is still very focused on ecological and technical considerations, impeding the understanding of how coral restoration can be used to improve reef resilience in the context of socio-ecological systems. Here, we visited four well-established coral restoration projects in different regions of the world (Thailand, Maldives, Florida Keys, and US Virgin Islands), and conducted key-informant interviews to characterize local stakeholder's perceptions of the key benefits and limitations associated with restoration efforts. Our results reveal that perceptions around coral reef restoration encompass far more than ecological considerations, and include all four dimensions of sustainability: ecological, social, economic, and governance, suggesting that effective coral restoration should be guided by the principles of sustainability science. Socio-cultural benefits were the most frequently mentioned (72.4% of all respondents), while technical problems were the most common theme for limitations of coral restoration efforts (58.3% of the respondents). Participants also revealed some key points likely to improve the outcomes of coral restoration efforts such as the need to better embrace socio-cultural dimensions in goal setting, evaluate ecological outcomes more broadly, secure long-term funding and improve management and logistics of day to day practices. While we identify several important limitations of coral reef restoration, particularly around amateur workforces and limited involvement of local communities, our results suggest that coral restoration can be used as a powerful conservation education tool to provide hope, enhance agency, promote stewardship and strengthen coral reef conservation strategies. Highlights: Perceptions around coral restoration include far more than only ecological concepts. Principles of sustainability science can help improve coral restoration outcomes. Local community involvement is important for the success of coral restoration effort. Technical problems and lack of capacity are the most common limitations to success. Coral restoration can be used as a powerful conservation education tool.